Speaker sex effects on temporal and spectro-temporal measures of speech. (21st March 2014) - Herrmann, Frank; Cunningham, Stuart P.; Whiteside, Sandra P.
<x content-type="archive" xml:space="preserve">Abstract</x> This study investigated speaker sex differences in the temporal and spectro-temporal parameters of English monosyllabic words spoken by thirteen women and eleven men. Vowel and utterance duration were investigated. A number of formant frequency parameters were also analysed to assess the spectro-temporal dynamic structures of the monosyllabic words as a function of speaker sex. Absolute frequency changes were measured for the first (F1), second (F2), and third (F3) formant frequencies (ΔF1, ΔF2, and ΔF3, respectively). Rates of these absolute formant frequency changes were also measured and calculated to yield measurements for rF1, rF2, and rF3. Normalised frequency changes (normΔF1, normΔF2, and normΔF3), and normalised rates of change (normrF1, normrF2, and normrF3) were also calculated. F2 locus equations were then derived from the F2 measurements taken at the onset and temporal mid points of the vowels. Results indicated that there were significant sex differences in the spectro-temporal parameters associated with F2: ΔF2, normΔF2, rF2, and F2 locus equation slopes; women displayed significantly higher values for ΔF2, normΔF2 and rF2, and significantly shallower F2 locus equation slopes. Collectively, these results suggested lower levels of coarticulation in the speech samples of the women speakers, and corroborate evidence reported in earlier studies.